Analysis of mobile applications reporting on nutritional recipes: a review of the scientific literature - Cabanillas-Carbonell, Michael (2021)
ABSTRACT At present the planet faces a pandemic originated by the COVID-19, causing social isolation and decrease in the world economy; limiting more and more the resources of many people, which produces a deficient feeding, In this document a systematic review of literature was made considering scientific articles between the years 2010 and 2020 from sources like, IEEE Xplore, Concytec, Proquest, Scopus, WoS and Scielo, having as objective to know the best characteristics of mobile applications to inform about nutritional recipes. A total of 50 articles were studied and it was concluded that there are databases with nutritional information of foods that help greatly in improving the nutrition of people, also found various techniques for obtaining data from new technologies.